Changes in photosynthetic capacity, carboxylation efficiency, and CO 2 compensation point associated with midday stomatal closure and midday depression of net - Tenhunen, J D; Lange, O L; Gebel, J (Planta, 1984)
The carbon-dioxide response of photo- synthesis of leaves of Quercus suber, a sclerophyl- lous species of the European Mediterranean re- gion, was studied as a function of time of day at the end of the summer dry season in the natural habitat. To examine the response experimentally, a "standard" time course for temperature and hu- midity, which resembled natural conditions, was imposed on the leaves, and the CO 2 pressure exter- nal to the leaves on subsequent days was varied. The particular temperature and humidity condi- tions chosen were those which elicited a strong sto- matal closure at midday and the simultaneous de- pression of net CO 2 uptake. Midday depression of CO 2 uptake is the result of i) a decrease in CO2- saturated photosynthetic capacity after light satu- ration is reached in the early morning, ii) a de- crease in the initial slope of the CO 2 response curve (carboxylation efficiency), and iii) a substantial in- crease in the CO 2 compensation point caused by an increase in leaf temperature and a decrease in humidity. As a consequence of the changes in pho- tosynthesis, the internal leaf CO 2 pressure re- mained essentially constant despite stomatal clo- sure. The effects on capacity, slope, and compensa- tion point were reversed by lowering the tempera- ture and increasing the humidity in the afternoon. Constant internal CO 2 may aid in minimizing photoinhibition during stomatal closure at midday. The results are discussed in terms of possible tem- perature, humidity, and hormonal effects on pho- tosynthesis.
Keywords: Carboxylation efficiency; Compensation point (CO2); Photosynthesis (temperature- humidity); Quercus; Sclerophyll